(untitled) (Experimental biology, 2018)
Restoration of oil-contaminated soils is an urgent task especially for oil-producing enterprises that are at risk of environmental pollution as a result of authorized and unauthorized disposal of oil spills, oil spills and other contingencies. Among the methods for reducing and eliminating soils and technogenic soils contamination with oil and oil products, microbiological, agro-phyto-meliorative and other methods of soil purification using high-quality oil sorbents are most effective. A promising unconventional ameliorant for oil-contaminated soils can be brown coals and shungites, which are both effective sorbents of toxicants and coal-humic fertilizers of soils - bioactivators. The purpose of the study was to study the process of bioremediation of oil contaminated soils on the basis of a natural and man-made carbonaceous bioactivator, the koksu shungite. For the first time, scientific research has been carried out on the effect of a natural bioactivator (koksu schungite, which is a muscovite-quartz-carbonaceous shale) and a technogenic bioactivator (a thermoactivated mechanical mixture of koksu shungite and oil) on the process of soil purification from crude oil extracted from the oil deposit "Elemes South" of the Mangistau region , as well as factors influencing the process of soil purification from petroleum hydrocarbons were revealed. The physicochemical characteristics of the oil and the microbiocenosis of the soils selected for the experiment were studied. The experimental soil samples were contaminated with oil to an environmentally hazardous state with an excess of permissible norms of 88.1 MPC. A model experiment consisting of two variants of the experiment was carried out: in the first variant of the experiment, a natural bioactivator was used - a mineral (shale schungite), in the second variant of the experiment - a technogenic bioactivator (thermoactivated at 600 oC mechanical mixture of cokshun shungite and oil). The use of schungite and the thermophilic regime favorably influence the process of bioremediation of soils from oil contamination, a high purification percentage is achieved - 97.3%. The results of the research made it possible to develop a method for bioremediation of oil-contaminated soils of a particular oil field "Elemes Southern" in the Mangistau region using a bioactivator - a coks schungite, which is a commodity product of the mining company "Koksu", the only industrial-developed deposit in Kazakhstan.